Calumenin-1 Interacts with Climp63 to Cooperatively Determine the Luminal Width and Distribution of Endoplasmic Reticulum Sheets - Birong Shen; Pengli Zheng; Nannan Qian; Qingzhou Chen; Xin Zhou; Junjie Hu; Jianguo Chen; Junlin Teng (iScience, 2019)
Summary: The ER is composed of distinct structures like tubules, matrices, and sheets, all of which are important for its various functions. However, how these distinct ER structures, especially the perinuclear ER sheets, are formed remains unclear. We report here that the ER membrane protein Climp63 and the ER luminal protein calumenin-1 (Calu1) collaboratively maintain ER sheet morphology. We show that the luminal length of Climp63 is positively correlated with the luminal width of ER sheets. Moreover, the lumen-only mutant of Climp63 dominant-negatively narrows the lumen of ER sheets, demonstrating that Climp63 acts as an ER luminal bridge. We also reveal that Calu1 specifically interacts with Climp63 and antagonizes Climp63 in terms of both ER sheet distribution and luminal width. Together, our data provide insight into how the structure of ER sheets is maintained and regulated. : Cell Biology; Membrane Architecture; Molecular Biology; Molecular Interaction; Organizational Aspects of Cell Biology Subject Areas: Cell Biology, Membrane Architecture, Molecular Biology, Molecular Interaction, Organizational Aspects of Cell Biology